The effect of a familiarization critical speed testing session on critical speed determination during treadmill running - Lorenzo Micheli; Tommaso Grossi; Silvia Pogliaghi; Francesco Lucertini; Carlo Ferri Marini (PLoS ONE, 2026)
Background The effect of familiarization with the critical speed (CS) testing process on the outcome of CS tests has yet to be determined. Objectives The main aims of the present study were to determine whether a familiarization session prior to CS testing sessions affects time to task-failure (TTF) on subsequent tests and CS estimations, and whether individual characteristics such as sex and fitness status influence any familiarization effect. Methods 27 healthy adults (10 females, 25 ± 4 yrs) performed the following treadmill protocol: i) a maximal incremental test to identify peak speed; ii) a familiarization constant-intensity trial (CT fam ) at the intensity of the first constant-intensity trial used for CS determination (CT CS ), and iii) four randomly ordered maximal constant-intensity trials at ~ 85%, 92%, 98%, and 105% of peak speed. CS was estimated using 2-parameter hyperbolic, linear, and 1/time models including the CT fam (CS not familiarized) or the CT CS (CS familiarized). Familiarized and not-familiarized TTFs and CSs were compared using Wilcoxon tests. Sex effect was analyzed using Mann-Whitney test on the difference in the TTF between CT CS and CT fam . The correlation between peak speed and difference in the TTF between CT CS and CT fam was assessed using Spearman’s rank correlation. α was set at 0.05. Results CT fam TTF (399 [299] s, median [interquartile range]) was lower (p = 0.009) than CT CS TTF (495[316] s), whereas CS familiarized and not-familiarized were not different in any model (p > 0.05). Sex did not affect the differences between familiarized and not-familiarized TTFs and CS. However, differences in the TTF between CT CS and CT fam were negatively correlated with peak speed (ρ = −0.381, p = 0.050). Conclusions Familiarization with constant-intensity trials affected the TTF but not CS. Importantly, the familiarization effect was larger in less fit individuals, showing a negative correlation between the TTF differences (i.e., CT CS minus CT fam ) and peak speed.